1995
DOI: 10.1111/j.1440-1754.1995.tb00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological outcome of ECMO‐eligible neonates with severe respiratory failure treated using conventional medical therapy

Abstract: Improvements to conventional treatments indicate that ECMO eligibility criteria may need to be revised to identify accurately those infants who are at extreme risk of mortality if treated conventionally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Developmental follow-up studies on these children have indicated survival rates of about 80% and 10 to 20% rates of long-term neurodevelopmental sequelae (Wildin et al 1994, Geven et al 1995, Mathias et al 1995. The largest outcome study to date (Glass et al 1995), with a total of 103 children seen at age 5 years, found a survival rate of 83% at discharge.…”
mentioning
confidence: 99%
“…Developmental follow-up studies on these children have indicated survival rates of about 80% and 10 to 20% rates of long-term neurodevelopmental sequelae (Wildin et al 1994, Geven et al 1995, Mathias et al 1995. The largest outcome study to date (Glass et al 1995), with a total of 103 children seen at age 5 years, found a survival rate of 83% at discharge.…”
mentioning
confidence: 99%